Study of Stevia (Stevia rebaudiana Bertoni) as a natural sweetener and its use in benefit of the health - Salvador-Reyes, Rebeca (2014)
Stevia, also known as "The miracle sweetener", is considered the best sugar substitute because it is up to 300 times sweeter and contains no calories. This shrub, grown in the forests of Brazil and Paraguay, has in its composition a high percentage of steviol glycosides (stevioside and rebaudioside A), which give it an intensely sweet taste and therapeutic properties against diabetes, hypertension and obesity also helps control weight, satiety and hunger. For its content in phenolic compounds, Stevia also acts as an excellent antioxidant and anticarcinogenic; also has been shown to have antibacterial, contraceptive, and diuretic properties. This review paper aims to collect information on the studies undertaken to stevia as an alternative to sugar and the benefits it provides consumption.